Lockdown, Earnings Losses and Household Asset Buffers in Europe. (23rd May 2022) - Kuypers, Sarah; Marx, Ive; Nolan, Brian; Palomino, Juan C.
Abstract: Measures taken to contain the spread of COVID‐19 affected some workers' capability to work and hence earning more than others. The initial impact may have been mitigated, for instance by relying on savings and assets, but access to these buffers likely varied within and across countries. In this article we estimate COVID‐19 potential earnings losses using the Lockdown Working Ability Index and relate this to households' savings and assets observed in the Eurosystem Household Finance and Consumption Survey. We find that, without government support, households in the Euro Area could only offset on average half of their losses by relying on liquid assets and almost half would deplete their savings in doing so, although there is significant cross‐country variation. When considering the effect of income support policies, liquid assets cover on average 65 percent of the remaining losses and still 20 percent would exhaust their liquid assets on average in the Euro Area.